Systemic Treatment with Nicotinamide Riboside Is Protective in Two Mouse Models of Retinal Ganglion Cell Damage - Zhang, Xian; Zhang, Nan; Chrenek, Micah A.; Girardot, Preston E.; Wang, Jiaxing; Sellers, Jana T.; Geisert, Eldon E.; Brenner, Charles; Nickerson, John M.; Boatright, Jeffrey H.; Li, Ying (Pharmaceutics, 2021)
Glaucoma etiology often includes retinal ganglion cell (RGC) death associated with elevated intraocular pressure (IOP). However, even when IOP is managed well, disease can progress. It is thus important to develop therapeutic approaches that directly protect RGCs in an IOP-independent manner. Compromised nicotinamide adenine dinucleotide (NAD+) metabolism occurs in neurodegenerative diseases, including models of glaucoma. Here we report testing the protective effects of prophylactically systemically administered nicotinamide riboside (NR), a NAD+ precursor, in a mouse model of acute RGC damage (optic nerve crush (ONC)), and in a chronic model of RGC degeneration (ocular hypertension induced by intracameral injection of microbeads). For both models, treatment enhanced RGC survival, assessed by counting cells in retinal flatmounts immunostained for Brn3a+. In the ONC model, treatment preserved RGC function, as assessed by pattern electroretinogram, and suppressed retinal inflammation, as assessed by immunofluorescence staining of retinal fixed sections for glial fibrillary acidic protein (GFAP). This is the first study to demonstrate that systemic treatment with NR is protective in acute and chronic models of RGC damage. The protection is significant and, considering that NR is highly bioavailable in and well-tolerated by humans, may support the proposition of prospective human subject studies.